Seleksi Bakteri Endofit Penghasil Senyawa Metabolit untuk Pengendalian Cendawan Patogen Terbawa Benih Jagung - Andini Hanif; Bonny Poernomo Wahyu Soekarno; Abdul Munif (Jurnal Fitopatologi Indonesia, 2016)
Endophytic bacteria have been reported to produce metabolite as antifungal compound. This study was aimed to obtain endophytic bacteria which are able to produce metabolite to control Fusarium sp., a potential seedborne fungi on maize. Endophytic bacteria were screened by hypersensitive test on tobacco leaves and antagonistic test. Endophytic bacteria isolates with high growth inhibitor activity were selected and examined for their metabolite compound. Thre isolates, i.e. Lactobacillus sp. isolate EF14III, Pseudomonas sp. isolate ER1I, dan Aeromonas sp. isolate ER10I has the potential to inhibit Fusarium sp..  Metabolite compound of Pseudomonas sp. isolates ER1I was able to decrease the infection Fusarium sp. by 65.0% in blotter test and decreased infection of Fusarium sp. up to 59.5% and 60.5% in growing on test using water agar and sterile soil, respectively.  Cyclohexanone with concentration of 9.68% produced by Pseudomonas sp. isolat ERI1 may play a role as antifungal compound.